In vivo detection of reduced Purkinje cell fibers with diffusion MRI tractography in children with autistic spectrum disorders - Jeong, Jeong-Won; Tiwari, Vijay N.; Behen, Michael E.; Chugani, Harry T.; Chugani, Diane C. (Frontiers in Human Neuroscience, 2014)
Postmortem neuropathology studies report reduced number and size of Purkinje cells (PC) in a majority of cerebellum specimens from persons with autism spectrum disorders (ASD). In this study using diffusion weighted MRI, we investigated whether structural changes related to decreased number and size of PC could be detected in vivo by measuring streamlines connecting the posterior-lateral region of the cerebellar cortex to the dentate nucleus using an independent component analysis with a ball and stick model (ICA+BSM). The tractography was performed in 14 typically developing children (TD) and 15 children with ASD, using a cerebellar cortex seed region (crus I and II) and two sorting regions, the dorsal dentate nucleus (DDN) and the ventral dentate nucleus (VDN). Decreased numbers of streamlines were found in the children with ASD in the pathway connecting cerebellar cortex to right VDN (p-value = 0.015). Reduced fractional anisotropy values were observed in pathways connecting the cerebellar cortex to the right DDN (p-value=0.008), the right VDN (p-value=0.010) and left VDN (p-value=0.020) in children with ASD compared to the TD group. In an analysis of single subjects, reduced FA in the pathway connecting cerebellar cortex to the right VDN was found in 73% of the children in the ASD group using a threshold of 3 standards errors of the TD group. The detection of diffusion changes in cerebellum may provide an in vivo biomarker of Purkinje cell pathology in children with ASD.